Testing the Bhaduri-Marglin model for the demand regime of Greece - Emilia G. Marsellou (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
This paper investigates the demand regime of the Greek economy for the period 1960-2017, using a Bhaduri/Marglin (1990) type macroeconomic demand-led model and applying the empirical methodology developed in Stockhammer et al. (2009). The analysis finds that Greece is another European economy with a wage-led demand regime, both domestically and as an open economy. Moreover, the analysis shows that the results are robust across different sample sizes, for the period 1960-2017, and the two sub-periods 1960-1989 and 1990-2017.
Keywords: E12; E20; E21; E25; F40; 330; Functional income distribution; Demand regimes; Consumption; Investment; Foreign trade; Greece; Wage moderation